2014
DOI: 10.1007/s10654-014-9886-3
|View full text |Cite
|
Sign up to set email alerts
|

Is herbal tea consumption a factor in endemic nephropathy?

Abstract: Endemic (Balkan) nephropathy (EN) is a chronic tubulointerstitial nephropathy frequently associated with upper urothelial cancer exclusively affecting farming villagers [1,2,3]. Based on our results, EN is considered to be an environmental form of aristolochic acid nephropathy (AAN) [1,2.3]. AAN was first reported in 1993 in Belgium and subsequently more AAN cases were reported worldwide as AA has been an integral part of traditional herbal medicines [4]. The extent of this problem was recently documented in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…For additional EJE references see [10,126,128,142,240,[453][454][455][456][457][458][459][460][461][462][463][464][465][466][467][468].…”
Section: New Developmentsmentioning
confidence: 99%
“…For additional EJE references see [10,126,128,142,240,[453][454][455][456][457][458][459][460][461][462][463][464][465][466][467][468].…”
Section: New Developmentsmentioning
confidence: 99%
“…34 It was questioned whether bread consumption was the only route of AA ingestion in BEN patients in the past. Although reports from Romania suggested that herbal medicine also might be a risk factor for AA exposure in BEN, 35 Ivkovi c et al, 36 in a large cohort of more than 2,500 Croatian farmers, rejected this hypothesis and confirmed that the use of herbs and herbal teas was not associated with BEN. Gruia et al 37 and Pavlovi c et al 38 speculated whether other plants (maize and cucumber) were capable of absorbing AA and thus being a secondary source of food poisoning.…”
Section: Epidemiology and Etiology Of Benmentioning
confidence: 97%
“…Aristolochic acid, AAI (8-methoxy-6-nitro-phenthro-(3,4- d )-1,3-dioxole-5-carboxylic acid) and aristolochic acid, AAII (6-nitro-phenthro-(3,4- d )-1,3-dioxole-5-carboxylic acid) are major components of aristolochic acid derived from Aristolochia species. They are contaminants of wheat grown in the Balkans and are also constituents of herbal teas . AAI is the cause of a rapidly progressive renal fibrosis and predisposes exposed individuals to urothelial tract carcinoma and bladder cancer .…”
Section: Substrates For Nitroreductasesmentioning
confidence: 99%